Biomarkers and Alzheimer’s disease: a bibliometric analysis - Yang, Linyi; Zeng, Jingyan; Li, Linlin; Zhang, Yunwei (Frontiers in Aging Neuroscience, 2024)
ObjectiveThe diagnosis and treatment of biomarkers in Alzheimer’s disease has emerged as a prominent topic within Alzheimer’s disease research. In this paper, we conducted a bibliometric analysis of data from a wide range of literature in this field to enhance the in-depth understanding of this area.MethodThe core collection of the Science Citation Index database (web of science) was used to search for relevant literature in the above fields from 1 January 2006 to 14 November 2022 and Citespace software was used to visualize and analyze the literature data.ResultsA total of 1,138 papers were included, of which the United States ranked first with 607 papers and China ranked 6th in the world with 84 papers. The value of mediational centrality is 0.49 in the United States and 0.05 in China. In terms of the number of articles published by the research authors, the Swedish scholar Blennow Kaj ranks first with 82 articles published, and the scholars who rank second and third are Zetterberg Henrik (78 articles) and Morris John C (64 articles), respectively; in terms of the mediational centrality, the American scholar Trojanowski John Q ranked first in the world with 0.1, and the second and third ranked scholars were Blennow Kaj (0.09) and Zetterberg Henrik (0.06) respectively. Scholar JACK CR ranked first with 377 citation frequency. The journal NEUROLOGY is ranked first with 943 citations.ConclusionIn recent years, global research in the field of biomarkers related to Alzheimer’s disease has shown signs of softening, and the momentum of research has slightly diminished. However, this trend does not imply a decline in the quality of research. It is essential to enhance collaboration among countries, major research institutions, and scholars, with a particular emphasis on fostering international partnerships in the future.